Axially chiral dimethylaminobenzimidazoles and their preliminary evaluation as acyl-transfer reagents - Toman, Daniel; Nemec, Ivan; Kurka, Ondřej; Přibylka, Adam; Cankař, Petr (Organic & biomolecular chemistry, 2025)
The synthesis of axially chiral benzimidazoles with a peri-substituted naphthalene and a dimethylamino group at positions 1 and 2, respectively, was developed. We evaluated these compounds in the desymmetrization reaction of cis-tetrahydrophthalic anhydride with benzyl alcohol, as the nucleophilic sp2 imidazole nitrogen atom is able to catalyze the acyl-transfer reaction. The prepared benzimidazoles demonstrated catalytic activity and showed that their axial chirality impacts stereoselectivity.